Analysis of Alfa-Fetoprotein as A Staging Determiner of Hepatocellular Carcinoma Progresivity - Dahvia Nursriyanti; Ani Kartini; Mutmainnah Mutmainnah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Hepatocellular carcinoma (HCC) is the most common malignant tumor with a poor prognosis and is known as the silent killer. The currently recommended HCC staging system is Barcelona Clinic Liver Cancer (BCLC). The Alpha-fetoprotein (AFP) test is still used to manage HCC patients. The purpose was to find out the AFP comparations and to decide cut-off values for each stage according to BCLC. Cross-sectional retrospective study using secondary data from medical records of Outpatients Clinic and Inpatients from January 2016 to October 2021 at Dr. Wahidin Sudirohusodo Hospital. A total of 432 samples based on BCLC were taken with AFP values and analyzed in this study. The male sample was 72.7%. The highest age is 46-65 years (62.7%). The etiology of HCC mostly is hepatitis B (72.5%). The most BCLC systems were BCLC B (53.7%), followed by BCLC A (25.9%), BCLC D (12.5%), and BCLC C (7.87%). There was a significant difference in AFP values between BCLC stages and the highest significance was BCLC D, followed by BCLC C, B, and A (p=0.05). The cut-off results values at the BCLC stage were BCLC A <21.84 ng/mL, BCLC B: 21.84 ng/mL (sensitivity 90.3%, specificity 85.7%), BCLC C: 478 ng/mL (sensitivity and specificity 100%), BCLC D: 7.693 ng/mL (sensitivity and specificity 100%). There was a significant difference in AFP values between BCLC stages and the highest is BCLC D. Based on the results of calculating the cut-off value, which has good sensitivity and specificity, AFP can be used as a determinant of stage progression of HCC.